Feuding, conflict, and banditry in nineteenth-century Corsica - Wilson, Stephen 1941- (Cambridge University Press, 1988)
Corsica is associated in many people's minds with vendetta and banditry, but these phenomena have not been studied systematically. Using accounts by visitors and officials and particularly judicial records, this book provides such a study for the nineteenth century. Accounts of specific feuds lasting over many generations are given, including that which inspired Mérimée's Colomba, and the whole phenomenon is set in its proper context of competition for scarce material resources and power in a traditional agro-pastoral society. Attitudes to death and the dead are examined, and reveal a divergence between local practice and belief and official Christianity, and the persistence of the notion that the spirit of the slain requires to be placated with blood. A general theme is the impact upon an isolated traditional society, and its system of sanctions, of incorporation into a modern state with courts and police